2018
DOI: 10.1016/j.healun.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes related to the complement system and antibody-mediated cardiac allograft rejection

Abstract: AMR is a complex phenotype affected by many recipient factors. Variants in p.Gly54Asp-MBL2 and p.Asn428(p=)-CFP genes, encoding mannose-binding lectin 2 and properdin, may influence the risk of AMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…16,23,24,26 Thus, complement genes related to AMR seem to be important in recipients, and not in donors, as we have previously noted. 10 In contrast, all of the studies carried out in genes related to B-cell biology in transplantation noted a relationship with various outcomes: acute rejection; 28,30-32,34-36 graft associated with the absence of AMR. No SNP, however, in complement pathway genes, either in donor or in recipientdonor pairs, was associated with AMR.…”
Section: Recipient-donor Genotype Discrepancy and Amrmentioning
confidence: 99%
See 3 more Smart Citations
“…16,23,24,26 Thus, complement genes related to AMR seem to be important in recipients, and not in donors, as we have previously noted. 10 In contrast, all of the studies carried out in genes related to B-cell biology in transplantation noted a relationship with various outcomes: acute rejection; 28,30-32,34-36 graft associated with the absence of AMR. No SNP, however, in complement pathway genes, either in donor or in recipientdonor pairs, was associated with AMR.…”
Section: Recipient-donor Genotype Discrepancy and Amrmentioning
confidence: 99%
“…10 All samples were included in the next-generation sequencing (NGS) study using the TruSight One panel according to manufacturer instructions (Illumina, San Diego, CA, USA). The TruSight One is a commercial NGS panel for the targeted genomic enrichment of 4,813 genes including 51 genes related to the complement pathway and 61 genes related to the biology of B cells ( Table S1).…”
Section: Targeted Next-generation Sequencing Genetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Lowered concentrations in the blood may also indicate a problem with the properdin-producing cells as in neutropenia [ 9 ]. Few studies also found increased systemic properdin levels (Table 1 ), for example in IgA nephropathy and in patients on hemodialysis [ 15 , 18 , 22 , 97 , 98 ]. The observation that increased properdin levels were associated with cardiovascular events and reduced levels with chronic heart failure was somewhat contradicting and needs further examination [ 16 , 98 ].…”
Section: Clinical Significance Of Properdinmentioning
confidence: 99%